Likelihood of Succession and Farmers’ Attitudes towards their Future Behaviour: Evidence from a Survey in Germany, the United Kingdom and Portugal - Sottomayor, Miguel; Tranter, Richard; Costa, Leonardo (The International Journal of Sociology of Agriculture and Food, 2011)
Most authors have referred to the likelihood of having an identified successor in the family as an influential factor affecting several family farm management decisions. Here, we investigate this relationship for a selection of such decisions: the timing of farmers’ retirement; the willingness of farmers to change their current mix of activities; their readiness to adopt new farm activities; and their attitude towards intensifying production. The categorical data analysed, mostly Likert scales, came from a postal survey carried out in 2001–2002 of a sample of 13,516 German, British and Portuguese farmers, with just over 4,600 valid responses. Statistical association between the variables was examined by computing the ?2 statistic and testing for the null hypothesis of no association between the various pairs of variables.The main conclusions are that the likelihood of having a successor was positively related to the planned length of active farmers’ lives, to farmers’ adoption of new activities, and to farmers’ willingness to intensify production in the future. The likelihood of having a successor was also found to be negatively related to the intention of leaving farm land idle. However, no empirical evidence was found of a statistically significant relationship between the likelihood of succession and farmers’ readiness to change the mix of their future farm activities.